Shielding without a Shield—Older People under COVID-19: A Comparison of Four Cities - Johnston H. C. Wong; Ghee W. Ho (Social Sciences, 2022)
Older people were globally the most vulnerable during the pandemic. This paper examines the mortality and psychological crisis of older people during the pandemic in four cities, namely Wuhan, Milan, London, and Hong Kong, in order to explain their high death rates. The sample cities were purposefully selected to cover different degrees of social connectedness and outbreak periods. Quantitative data were employed to account for death and suicide data. Qualitative data analyses in government reports, public press releases, NGO announcements, and journal articles were used to study government responses and disruptions of essential healthcare services. Published scientific studies provided important information on the psychological stress and resilience of older people. Findings based on a welfare regime perspective showed that society and governments have not learned from the experiences of other countries, which resulted in high numbers of preventable deaths. Older people have successfully coped with living difficulties while serious psychological disturbances and suicidal ideations were absent at least for the period up to 2022. Older care home residents, unfortunately, were not protected with proper shielding and available vaccinations. Public inefficiency and negligence contributed to a disproportionately high rate of mortality in nursing homes.